Farmers’ Perception on Climate Change Impacts on Coffee Farming: A Case Study of Gayo Highlands, Aceh, Indonesia - Wijaya, Laila; Karim, Abubakar; Hasyim, Wardah (HABITAT, 2024)
In Aceh, Indonesia, climate change is predicted to reduce land availability and suitability for Arabica coffee production by 90% by 2050. Arabica coffee farming is and will be more impacted by climatic events as a result of such climate change among commercial crops. This study examines how coffee farmers in Aceh Tengah and Bener Meriah (Gayo Highlands), two of Indonesia's major Arabica coffee producing areas, perceive changes in climate, their personal susceptibility to the impacts of climate change, and their coping/adaptation strategies. Focus Group Discussions were carried out with twenty-eight coffee farmers and ten local experts were interviewed to gain information on the topics. The data analysis from FGD and interviews show the multiple stresses of rainfall and temperature on Arabica coffee productivity in Gayo Highlands. Findings indicate that coffee producers have only moderate concerns about climate issues despite the harm climate change poses to the industry. The continuous and current effects of climate change may endanger coffee production and its sustainability in Gayo Highlands, thereby highlighting the potential for negative impacts on the livelihoods of local communities, which could further exacerbate the welfare challenges faced by their families.  A number of suggestions were made to help the parties involved create better adaptation plans that are tailored to the needs, interests, and capacities of the farmers.